2016
DOI: 10.1182/blood-2015-09-671420
|View full text |Cite
|
Sign up to set email alerts
|

Sustained correction of FVII deficiency in dogs using AAV-mediated expression of zymogen FVII

Abstract: • Dogs with an FVII G96E mutation (FVII-G96E) represent the most common human FVII mutation type and are ideal for testing new therapies.• cFVII gene delivery in FVII-G96E dogs via AAV at a dose effective in humans showed stable and clinically therapeutic FVII expression.Factor VII (FVII) deficiency is a rare autosomal recessive bleeding disorder treated by infusion of fresh-frozen plasma, plasma-derived FVII concentrates and low-dose recombinant activated FVII. Clinical data suggest that a mild elevation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…49 According to clinical results from application of rFVIIa, gene therapy using an AAV vector to deliver FVIIa has been tested in animal models with hemophilia, and phenotypic correction has been achieved. 27,42,50 Consistent with previous studies, improved hemostasis was observed when AAV9 encoding mouse FVIIa was administered into hemophiliac mice with FVIII inhibitor. Collectively, these results suggest that delivery of FVIIa utilizing alternative AAV serotypes without cross-reactivity is a novel approach to treat hemophilia in patients with preexisting neutralizing antibodies to AAV and inhibitory antibodies to the deficient coagulation factor.…”
Section: Discussionsupporting
confidence: 84%
“…49 According to clinical results from application of rFVIIa, gene therapy using an AAV vector to deliver FVIIa has been tested in animal models with hemophilia, and phenotypic correction has been achieved. 27,42,50 Consistent with previous studies, improved hemostasis was observed when AAV9 encoding mouse FVIIa was administered into hemophiliac mice with FVIII inhibitor. Collectively, these results suggest that delivery of FVIIa utilizing alternative AAV serotypes without cross-reactivity is a novel approach to treat hemophilia in patients with preexisting neutralizing antibodies to AAV and inhibitory antibodies to the deficient coagulation factor.…”
Section: Discussionsupporting
confidence: 84%
“…This dose is equivalent to 4.35 × 10 13 GC/kg based on the average weight of an 8-week-old mouse (23 g). Although this dose appears to be high, a preclinical study in dogs using semi-systemic intraportal administration of rAAV8 reported the safe administration of 4.95 × 10 13 GC/kg, supporting the safety and feasibility of our dose26. Interestingly, Chuhong Hu et al .…”
Section: Discussionsupporting
confidence: 57%
“…Novel agents such as long-acting molecules with improved half-life have been developed by means of different strategies including the fusion technology [25,26], and pro-coagulant factors such as FVIIa, FX or FV with enhanced biological properties have been engineered for the treatment of hemophilia [27]. Finally, for hemophilia patients, gene therapy is a potential new option with growing evidence of efficacy (excellently reviewed in [27]), even if very interesting data have been obtained in two animal models of FVII deficiency [28,29].…”
Section: Blood Coagulation and Hemorrhagic Disordersmentioning
confidence: 99%
“…Not surprisingly, advances in hemophilia B gene therapy increased research in other coagulation disorders, even in the rare ones transmitted as autosomal recessive traits. This is the case of FVII deficiency, in which AAV-mediated gene therapy has been evaluated in a natural canine model through the expression of canine FVII transgene as well as exploiting codon-optimized human FVII in adult macaques, with very promising data on the longevity and stability of therapeutic levels of FVII expression in the absence of side-effect complications [28,29,42,43].…”
Section: Overview Of Correction Approaches At Dna Mrna and Proteimentioning
confidence: 99%